Application of a high-performance liquid chromatography method for the evaluation of non-provitamin A carotenoids - Titcomb, Tyler J.; Davis, Christopher R.; Tanumihardjo, Sherry A. (2017)
Biofortification of maize with provitamin A carotenoids is an emerging intervention for providing vitamin A to people where maize is a staple crop. Analyzing the effectiveness of biofortified maize adoption will be important in the coming years. We propose that serum carotenoid profiles will be ideal for this endeavor. The C30 HPLC column was developed specifically for carotenoid separations because the longer alkyl chains provide better separation of carotenoids and their respected isomers. Most types of maize that have been released also have enhanced concentrations of the xanthophyll carotenoids lutein and zeaxanthin. Due to the chemical similarity of lutein and zeaxanthin, the C30 column is ideal for analysis because it is capable of maintaining separation of these two non-provitamin A carotenoids. A potential drawback of the C30 column is longer analytical time specifically for lycopene. When monitoring study subject low carotenoid diets during a human maize feeding trial, we prop